Investigations on micro-mechanical properties of polycrystalline Ti(C, N) and Zr(C, N) coatings. (1st May 2018) - El Azhari, Idriss; Garcia, José; Zamanzade, Mohammad; Soldera, Flavio; Pauly, Christoph; Llanes, Luis; Mücklich, Frank
Abstract: Micro-mechanical properties of Ti(C, N) and Zr(C, N) coatings deposited by chemical vapor deposition on a WC-Co cemented carbide substrate were examined by micro-compression testing using a nanoindenter equipped with a flat punch. Scanning Electron Microscopy, Focused Ion Beam, Electron Backscattered Diffraction and Finite Element Modeling were combined to analyze the deformation mechanisms of the carbonitride layers at room temperature. The results revealed that Ti(C, N) undergoes a pure intergranular crack propagation and grain decohesion under uniaxial compression; whereas the fracture mode of Zr(C, N) was observed to be inter/transgranular failure with unexpected plastic deformation at room temperature. Graphical abstract: Image 1